2005
DOI: 10.1007/s10566-005-7753-9
|View full text |Cite
|
Sign up to set email alerts
|

That’s Not My Problem: Convergence and Divergence Between Self- and Other-Identified Problems Among Homeless Adolescents

Abstract: Mental health symptoms, victimization experiences, and rates of substance use among homeless youth were assessed using typical clinical intake questions and standard questionnaires. Youth were also asked what they regarded as their primary problems. Results indicated that issues likely to concern health professionals, such as past victimization, high rates of substance use, and psychological symptoms, are often not regarded as problems by homeless youth. Also, based on responses to a coping interview, homeless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Use of substances may be an important coping mechanism among these youth to decrease, change, or escape memories of childhood trauma; strains faced while homeless; and trauma and emotional discomfort associated with engagement in sexual risk behaviors or experience of victimization. Although there is limited extant research examining coping among homeless youth, findings of these studies have generally shown substances are used by this population group to manage their feelings, psychological distress, and emotional discomfort (Fisher, Florsheim, & Sheetz, 2005;Kidd, 2003;Rhule-Louie, Bowen, Baer, & Peterson, 2008). There is a need to understand the role using substances may have in relation to sexual risk behavior and sexual victimization.…”
Section: Discussionmentioning
confidence: 99%
“…Use of substances may be an important coping mechanism among these youth to decrease, change, or escape memories of childhood trauma; strains faced while homeless; and trauma and emotional discomfort associated with engagement in sexual risk behaviors or experience of victimization. Although there is limited extant research examining coping among homeless youth, findings of these studies have generally shown substances are used by this population group to manage their feelings, psychological distress, and emotional discomfort (Fisher, Florsheim, & Sheetz, 2005;Kidd, 2003;Rhule-Louie, Bowen, Baer, & Peterson, 2008). There is a need to understand the role using substances may have in relation to sexual risk behavior and sexual victimization.…”
Section: Discussionmentioning
confidence: 99%
“…A dominant narrative reflected in research regarding homeless youth is one of a problem-focused tone. Indeed, homeless youth face considerable risks and adverse experiences, including physical and sexual abuse (Fisher, Florsheim, & Sheetz, 2005; Keeshin & Campbell, 2011), street-based victimization (Stewart et al, 2004; Thrane, Hoyt, Whitbeck, & Yoder, 2006; Tyler, Hoyt, Whitbeck, & Cauce, 2001), and suicidal ideation (Kidd & Carroll, 2007; Rohde, Noell, Ochs, & Seeley, 2001). Moreover, because of negative experiences both prior to leaving home and those further encountered once homeless, these youth frequently meet diagnostic criteria for a number of mental disorders, including depressive disorder (Rohde et al, 2001; Unger et al, 1998) and/or substance use disorder (Mallett, Rosenthal, Myers, Milburn, & Rotheram-Borus, 2004; Thompson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These findings also reveal the violent contexts within which homeless youth often become pregnant (both before and after losing housing, and while living on the streets), including within dynamics of childhood sexual abuse and intimate partner violence (IPV). Research has consistently demonstrated that childhood violence and abuse is correlated with homelessness for young people (Fisher, Florsheim, & Sheetz, 2005; Keeshin & Campbell, 2011), and youth who are homeless experience high rates of violent victimization once on the streets (Bender et al, 2018; Coates & McKenzie-Mohr, 2010; Ensign & Santelli, 1998). Research also shows that the risk of experiencing IPV may actually increase when girls and women become pregnant (García-Moreno, Jansen, Ellsberg, Heise, & Watts, 2005).…”
Section: Discussionmentioning
confidence: 99%